Weather Affecting Macro-Moth Diversity at Khao Nan National Park, Thailand - JAROENSUTASINEE, Mullica; PHEERA, Wittaya; NINLAEARD, Ratree; JAROENSUTASINEE, Krisanadej; CHOLDUMRONGKUL, Surachai (Walailak Journal of Science and Technology (WJST), 2011)
Surveying on the diversity of the macro-moths was done at Khao Nan National Park, Nakhon Si Thammarat, Thailand from January 2007 to December 2008. We caught 57 species with 170 individuals of macro-moths covering nine families: Cossidae, Cyclidiidae, Eupterotidae, Geometridae, Lasiocampidae, Noctuidae, Saturniidae, Sphingidae and Uraniidae. We collected 46 species with 24 singletons and 123 individuals belonging to nine families at Headquarters and 24 species with 16 singletons and 47 individuals belonging to 6 families at Huilek Park Ranger station. Sphingidae was recorded as the most diverse family sampled in Khao Nan National Park, followed by Noctuidae, and Saturniidae. The macro-moths visited the light trap at Headquarters every month during the study period. The highest species richness was observed in June 2007 with 10 species. The number of macro-moths at Huilek Park Ranger station was highest in October and December 2007. The species composition in the Headquarters was approximately three times higher than at Huilek Park Ranger station. At Headquarters, the number of individual macro-moths was positively correlated with mean/max/min temperatures and negatively correlated with relative humidity and not associated with rainfall. On the other hand, the number of individual macro-moths at Huilek Park Ranger station was not associated with mean/max/min temperatures, relative humidity or rainfall.